Endophytic Fungi Isolated from Coleus amboinicus Lour Exhibited Antimicrobial Activity - Puji Astuti; Sudarsono Sudarsono; Khoirun Nisak; Giri Wisnu Nugroho (Tabriz University of Medical Sciences, 2014)
Purpose: Coleus amboinicus is a medicinal plant traditionally used to treat various diseases such as throat infection, cough and fever, diarrhea, nasal congestion and digestive problems. The plant was explored for endophytic fungi producing antimicrobial agents. Methods: Screening for endophytic fungi producing antimicrobial agents was conducted using agar plug method and antimicrobial activity of promising ethyl acetate extracts was determined by disc diffusion assay. Thin layer chromatography (TLC) - bioautography was performed to localize the bioactive components within the extract. TLC visualization detection reagents were used to preliminary analyze phytochemical groups of the bioactive compounds. Results: Three endophytic fungi were obtained, two of them showed promising potential. Agar diffusion method showed that endophytic fungi CAL-2 exhibited antimicrobial activity against P. aeruginosa, B. subtilis, S. aureus and S. thypi, whilst CAS-1 inhibited the growth of B. subtilis. TLC bioautography of ethyl acetate extract of CAL-2 revealed at least three bands exhibited antimicrobial activity and at least two bands showed inhibition of B. subtilis growth. Preliminary analysis of the crude extracts suggests that bioactive compounds within CAL-2 extract are terpenoids, phenolics and phenyl propanoid compounds whilst the antimicrobial agents within CAS-1 extract are terpenoids, propylpropanoids, alkaloids or heterocyclic nitrogen compounds. Conclusion: These data suggest the potential of endophytic fungi of C. amboinicus as source for antimicrobial agents.